An unusual location of gouty panniculitis: A case report. Issue 16 (April 2017) - Martin, David; Joliat, Gaëtan-Romain; Fournier, Pierre; Brunel, Christophe; Demartines, Nicolas; Gié, Olivier
Abstract: Rationale: Gouty panniculitis, characterised by the deposition of monosodium urate crystals in subcutaneous tissue, is a rare clinical manifestation of gout. Patient concerns: The case of a 67-year-old man is reported, who presented an erythematous nodule on the upper part of the right buttock suspicious for an abscess. This was in the context of chemotherapy for non-Hodgkin's lymphoma. Diagnoses: Histopathologic examination demonstrated gouty panniculitis. Interventions: Because infection was suspected, an incision was performed. The lesion was found to be densely calcified and friable, without purulent discharge. Therefore, a surgical en-bloc resection was performed. Outcomes: The wound healed slowly initially due to a combination of malnutrition, chemotherapy and infection. A wound infection with Enterococcus faecium was treated with antibiotic therapy (carbapenem for seven days) and local therapy. At 6-week follow up the wound showed good granulation tissue and was healing well by secondary intention. The patient was instructed to continue anti-hyperuricaemic treatment. Lessons subsections: In patients known to have long-standing hyperuricaemia and gout with nonspecific subcutaneous erythematous nodules, gouty panniculitis should be considered.